2013
DOI: 10.1021/cg4007197
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution upon Crystallization of 3D, Chiral Inorganic Networks Assembled from Achiral, Polyoxometallate Units and Metal Ions

Abstract: Two enantiomerically pure 3D chiral POM-based compounds 1a and 1b, having formula (H 3 O + ) 2 [K 2 (SiW 12 O 40 )-(H 2 O) 4 ]•H 2 O, have been isolated during crystallization. Single-crystal X-ray diffraction analysis revealed that 1a and 1b are enantiomers, crystallizing in chiral space groups P6 2 22 and P6 4 22, respectively. The compounds are optically active, and their UV spectra show Cotton effects in the opposite direction. Compounds 1a and 1b represent the examples of 3D chiral frameworks of POM-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…These crystals belong to the hexagonal system within either the chiral space groups P 6 2 22 (if the additive was Mn) or P 6 4 22 (if the additive was Eu). The presence of transition metal additives seems necessary for the spontaneous resolution (or symmetry breaking) since in their absence, a racemic CD silent mixture has been obtained …”
Section: Chiral Supramolecular Assemblies From Achiral Building Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…These crystals belong to the hexagonal system within either the chiral space groups P 6 2 22 (if the additive was Mn) or P 6 4 22 (if the additive was Eu). The presence of transition metal additives seems necessary for the spontaneous resolution (or symmetry breaking) since in their absence, a racemic CD silent mixture has been obtained …”
Section: Chiral Supramolecular Assemblies From Achiral Building Blocksmentioning
confidence: 99%
“…The presence of transition metal additives seems necessary for the spontaneous resolution (or symmetry breaking) since in their absence, a racemic CD silent mixture has been obtained. 501 Another case of possible symmetry breaking has been described by Yang et al 502 H 2 O in a molar ratio of 8:2:1 at 200 °C for 5 days. Homochirality of the single crystals of this copper borophosphate compound was checked by single-crystal X-ray diffraction analysis revealing a P2 1 2 1 2 1 space group, with a Flack parameter of 0.010(11).…”
Section: Polyoxometalatesmentioning
confidence: 99%
“…Chiral polyoxometalates (POMs) have received much attention, not only owing to their intriguing topologies and architectures, but also because of their significant potential applications in nonlinear optics, enantioselective catalysis, chiroptical switching, and medicine. The syntheses of chiral POMs can be realized either by enantioselective synthesis using enantiomerically pure chiral organic species and chiral metal–organic fragments, or by spontaneous resolution using achiral materials, generating a conglomerate (mixture of chiral crystals). Compared with the approach using expensive chiral auxiliary, spontaneous resolution upon crystallization is more appealing as an economical and convenient method. However, the laws of physics determining the processes have not yet been fully understood because of the unpredictability of crystal structures, and most POM clusters possess high symmetry, thus spontaneous resolution is still a relatively scarce phenomenon, confronting more difficulties and challenges.…”
Section: Introductionmentioning
confidence: 99%
“…[85][86][87] Hundal et al and other groups have reported spontaneous resolution of polyoxometalate based 3D MOFs. [88][89][90] Thus, conglomerate formation of MOFs comprising achiral precursors is an interesting alternative for the fabrication of chiral networks. Unfortunately, the mechanistic aspects of such crystallization events are little understood, hindering the implementation of this concept as a cheaper alternative for designing homochiral networks.…”
Section: Chiral Mofs From Achiral Precursors: Spontaneous Resolutionmentioning
confidence: 99%